Revisión de la literatura sobre redes sociales y entrepreneurship (2008)
This paper carries out a review of recent literature on enterprise networks. From an instrumental perspective, it is intended to integrate theoretical descriptions of how the content and structure of social networks contribute to the success of the activity of the entrepreneur. To that end, this review comes first exposing the different approaches to the study of the relationship between social networks and the entrepreneurial process. Later addressing the various typologies and existing definitions of the concept of social networking venture. Thirdly outlines 5 models that explain the relationship between the dynamics of networks and stages of evolution of the entrepreneurial process. Then this work addresses the instrumental role of networks for entrepreneurs in developing their business, focusing on explain how the entrepreneurs use the networks to obtain social and cognitive legitimacy. The review concludes by proposing some conclusions and elements to be considered in future research.